Provider and Patient Perceptions of an External Medication History Function. Issue 4 (December 2018) - Wolver, Susan E.; Stultz, Jeremy S; Aggarwal, Arpita; Thacker, Leroy; Banas, Colin
Abstract : Objectives: To determine the awareness and use of an external medication history (EMH) function within an electronic health record and its impact on patient perception of medication adherence. Methods: Two self-administered surveys were given: one to providers and one to patients. Participants included providers from an academic medical center and patients from 2 general internal medicine clinics. Results: Of 154 completed provider surveys, 61% were aware the EMH existed. More of the respondents aware of the EMH were primary care and medicine subspecialty providers (79.1%) when compared with surgical providers (20.9%, P < 0.0001). The most common reasons chosen for looking at the EMH included checking for medication adherence (44%), questions about a specific medication (40%), and checking controlled substance prescription history (37%). Of those aware of the EMH, 65% found medications on the EMH that they were not aware their patient was getting filled. Of the 94 patient surveys, 34% felt the EMH feature might change their medication taking behavior, and 48% responded that it already had. Patients with a history of depression and/or anxiety were less likely to report the intent to change their medication taking behavior, OR, 0.34 [95% CI, 0.13-0.87]. Conclusion: An external medication history function can provide further insight about a patient's medication profile and prescription filling. Knowledge attained from the EMH may improve patient safety by helping to uncover nonadherence, dosing discrepancies, and medications prescribed by other providers. Additionally, patient knowledge of this feature might improve medication adherence. Although further studies are needed to obtain objective data, the external medication history function may have significant impact on both providers and patients, and its benefit should be widely publicized.